Diseño y ejecución de plan de mantenimiento preventivo para el sistema de plantas eléctricas en el terminal de transporte de Neiva s.a. (2023)
Nowadays, the Terminal de Transporte de Neiva S.A. is in constant growth, which is why its set of electrical plants is of critical importance, therefore, the company requires a preventive maintenance plan to ensure the supply of electricity in the event of outages that may occur by the energy distribution company. Currently, the Terminal de Transporte de Neiva S.A. has a corrective maintenance plan (when the failure is already present) which causes unavailability in emergency cases, generating high maintenance costs, economic lossesfor not being able to perform its activities normally, for not having the necessary spare parts, since its focus is focused on solving only the failures that are found at that time, causing low rates of availability and reliability in the set of power plants of the Terminal de Transporte de Neiva S.A. This situation has led the company to consider an effective and immediate solution, for which it is proposed to implement a preventive maintenance plan based on reliability (RBM), once this preventive maintenance plan is implemented, it will be executed in the set of power plants installed in the Terminal de Transporte de Neiva S.A. With this implementation it is expected to increase the availability and reliability rates to 90%, it is also expected that the student will apply the knowledge acquired during his training as a Mechanical Engineer.